HUiTM mobile PPV outreach - Nik Mohd Nasir, Nik Munirah; Tharek, Zahirah; Kanoo, Lina Lohshini; Kamaruddin, Khairatul Nainey; Shibraumalisi, Nur Amirah; Miptah, Hayatul Najaa (Faculty of Medicine, 2021)
Amid the relentless crippling claws of COVID-19, rose a community drive aimed to arm the ‘already crippled’ in society, with the only armor humanity has in its defense against a raging pandemic war: the COVID – 19 vaccine. Inspired by a team of equally relentless primary care physicians, we embarked on a journey that took us from our campus clinic along city highways to a government health office and its neighboring health clinic, in the Selangor outskirts where the path was paved, to deliver the COVID -19 vaccine to the bedbound, immobilized, physically and mentally challenged: vulnerable members of our community, in areas of Kuala Selangor, Jeram and Puncak Alam.